The Impact of the adeE and adeY Genes on the Antibiotic Resistance Mechanisms of Acinetobacter baumannii - Rawaa M. Mohammed (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Current study identified Acinetobacter baumannii isolates from burn wound samples using biochemical andmolecular techniques focusing on the rpoB gene. All isolates showed variable virulence factors, includingbiofilm formation (100%), gelatinase activity (90%), and mannose-resistant hemagglutination (72%). Antibioticsusceptibility testing revealed high resistance rates to Rifampin (96%), Tetracycline (92%), and third-generation cephalosporins such as Cefotaxime (73%) and Ceftriaxone (81%). Lower resistance rates wereobserved for Levofloxacin (31%) and Gatifloxacin (27%), suggesting potential effectiveness.PCR analysis confirmed the presence of AdeE and AdeY efflux pump genes in several isolates. However,statistical analysis, including Chi-square/Fisher’s tests and t-tests, demonstrated no significant correlationbetween the presence of these genes and antibiotic resistance patterns (p > 0.05). This indicates that whileefflux pump genes are present, their presence alone does not predict antibiotic resistance in the tested isolates.The findings highlight the complex mechanisms of resistance in A. baumannii and the need for continuedsurveillance and molecular diagnostics to guide effective infection control.